2017
DOI: 10.1038/s41467-017-01836-2
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cpf1 mediates efficient homology-directed repair and temperature-controlled genome editing

Abstract: Cpf1 is a novel class of CRISPR-Cas DNA endonucleases, with a wide range of activity across different eukaryotic systems. Yet, the underlying determinants of this variability are poorly understood. Here, we demonstrate that LbCpf1, but not AsCpf1, ribonucleoprotein complexes allow efficient mutagenesis in zebrafish and Xenopus. We show that temperature modulates Cpf1 activity by controlling its ability to access genomic DNA. This effect is stronger on AsCpf1, explaining its lower efficiency in ectothermic orga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
291
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(306 citation statements)
references
References 37 publications
13
291
1
1
Order By: Relevance
“…Therefore, we tested whether LbCas12a (Zetsche et al ., ), with its thymine rich PAM (TTTV), which occurs also more frequent, can serve as an efficient alternative nuclease for in planta GT. In addition, testing Cas12a variant was especially interesting as other reports, unfortunately based on very small numbers of GT events, claimed that the use of Cas12a as a nuclease might result in higher GT frequencies than the use of Cas9 (Begemann et al ., ; Ferenczi et al ., ; Moreno‐Mateos et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, we tested whether LbCas12a (Zetsche et al ., ), with its thymine rich PAM (TTTV), which occurs also more frequent, can serve as an efficient alternative nuclease for in planta GT. In addition, testing Cas12a variant was especially interesting as other reports, unfortunately based on very small numbers of GT events, claimed that the use of Cas12a as a nuclease might result in higher GT frequencies than the use of Cas9 (Begemann et al ., ; Ferenczi et al ., ; Moreno‐Mateos et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…CRISPR-Cas12a (formerly known as Cpf1) is a class 2 type V CRISPR system that has been adopted for genome engineering in several organisms (Zetsche et al 2015;Moreno-Mateos et al 2017;Malzahn et al 2019;Chow et al 2019). Cas12a is a RNA-guided DNA endonuclease with a number of attributes distinct from Cas9, making it an interesting candidate to complement the CRISPR toolbox also in Drosophila.…”
Section: Introductionmentioning
confidence: 99%
“…We previously assessed Cas12a performance in Drosophila focused exclusively on AsCas12a and reported low activity compared to SpCas9 (Port and Bullock 2016). A subsequent study in zebrafish and Xenopus demonstrated that Cas12a activity is strongly temperature-dependent and showed that AsCas12a has low activity at temperatures below 30°C (Moreno-Mateos et al 2017). This is likely to limit the utility of AsCas12a in Drosophila, which do not tolerate long-term exposure to temperatures above 30°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the protospacer-adjacent motif (PAM) of Cas12a is Trich in comparison to the G-rich PAM of Cas9 which identifies more possible target sequences near STOP codons of mammalian cells (Buchmuller et al, 2019). In addition, Cas9 induces DSBs close to the PAM site while Cas12a cuts further away from it, which might increase targeting efficiency as the target sequence is not as easily destroyed by indel formation and may be re-cleaved after repair (Zetsche et al, 2015;Moreno-Mateos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%